Pharmacotherapy of Posttraumatic Cognitive Impairments - David B. Arciniegas; Jonathan M. Silver (Behavioural Neurology)
Pharmacotherapy may contribute to the rehabilitation of persons with posttraumatic cognitive impairments. This article reviews first the neurobiological consequences of traumatic brain injury with a particular emphasis on acute and long-term posttraumatic neurochemical disturbances. Studies of pharmacotherapies for posttraumatic cognitive impairments are reviewed next, and are organized according to medication class and the neurotransmitter system they affect most. Based on the evidence provided by that review, augmentation of posttraumatic cerebral catecholaminergic and cholinergic function are suggested as potentially useful neurochemical targets for pharmacologic intervention in this population. More specifically, it is suggested that persons with posttraumatic impairments in arousal, speed of processing, and possibly attention may benefit most from treatment with an agent that augments cerebral catecholaminergic function, and that persons whose predominant posttraumatic impairment is in the domain of memory may benefit most from treatment with cholinesterase inhibitors. Practical considerations regarding the use of pharmacotherapies for posttraumatic cognitive impairments are offered, and the need for additional research in this area is highlighted.